Hispanic american independence: New perspectives - Martínez-Flener, Milagros (2022)
Research on Hispanic American independence usually uses documentation from Spanish and Latin American archives, not taking into account that of those European countries considered outside the orbit of the Hispanic monarchy. The funds of the Austrian State Archives allow us to analyze the theme of the independence using the correspondence of the diplomatic representatives of the Austrian empire stationed in Spain and Brazil. The reports, sent to Vienna between 1808 and 1825, at a time when virtually all of Europe was mired in war, open a new perspective in the investigation on the independence activities. While the documentation of the Austrian representatives in Spain offers the possibility of analysing the American independence movement from within the Spanish crown itself, the reports coming from Brazil allow the access to information from those Austrian diplomats who were geographically closer to the events in South America and who informed to Vienna about the Portuguese position on the insurgence of the Spanish colonies, an aspect little dealt with until now by the historiography. These reports offer the possibility of taking into account new aspects that would enrich the research on Spanish American independence.